1850 Mass. Acts 401, § 1 - (:unkn) unknown (My University, 1850)
Ch. 194, §1: Anyone arrested and armed with any dangerous weapon, of the kind usually called a slung-shot, shall be punished by a maximum fine of fifty dollars or imprisonment not exceeding one year.
Keywords: POSSESSION - NON-GUN ARMS